Acute pancreatitis: current perspectives on diagnosis and management - Shah AP (Dove Medical Press, 2018)
Adarsh P Shah, Moustafa M Mourad, Simon R Bramhall Department of Surgery, Hereford County Hospital, Hereford, UK Abstract: The last two decades have seen the emergence of significant evidence that has altered certain aspects of the management of acute pancreatitis. While most cases of acute pancreatitis are mild, the challenge remains in managing the severe cases and the complications associated with acute pancreatitis. Gallstones are still the most common cause with epidemiological trends indicating a rising incidence. The surgical management of acute gallstone pancreatitis has evolved. In this article, we revisit and review the methods in diagnosing acute pancreatitis. We present the evidence for the supportive management of the condition, and then discuss the management of acute gallstone pancreatitis. Based on the evidence, our local institutional pathways, and clinical experience, we have produced an outline to guide clinicians in the management of acute gallstone pancreatitis. Keywords: acute pancreatitis, severity scoring, diagnostic imaging, management of gallstone pancreatitis